2009
DOI: 10.1162/jocn.2009.21080
|View full text |Cite
|
Sign up to set email alerts
|

N250 ERP Correlates of the Acquisition of Face Representations across Different Images

Abstract: We used ERPs to investigate neural correlates of face learning. At learning, participants viewed video clips of unfamiliar people, which were presented either with or without voices providing semantic information. In a subsequent face-recognition task (four trial blocks), learned faces were repeated once per block and presented interspersed with novel faces. To disentangle face from image learning, we used different images for face repetitions. Block effects demonstrated that engaging in the face-recognition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
133
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 169 publications
(161 citation statements)
references
References 57 publications
26
133
2
Order By: Relevance
“…This shows that the N250 reflects the activation of long-term face memory as well as the activation of a recently learned representation of a previously unfamiliar face in short-term memory. The N250 to participants' own face was already present in the first half of the experiment, while the N250 to target faces only emerged during the second half, suggesting that an episodic representation of a previously unfamiliar target face builds up gradually (see also Kaufmann, Schweinberger, & Burton, 2009). Target Faces and Own faces also elicited a sustained positivity that peaked around 500 ms post-stimulus in the study by studies of famous face recognition (Gosling & Eimer, 2011;Eimer et al, 2012).…”
Section: Introductionmentioning
confidence: 77%
“…This shows that the N250 reflects the activation of long-term face memory as well as the activation of a recently learned representation of a previously unfamiliar face in short-term memory. The N250 to participants' own face was already present in the first half of the experiment, while the N250 to target faces only emerged during the second half, suggesting that an episodic representation of a previously unfamiliar target face builds up gradually (see also Kaufmann, Schweinberger, & Burton, 2009). Target Faces and Own faces also elicited a sustained positivity that peaked around 500 ms post-stimulus in the study by studies of famous face recognition (Gosling & Eimer, 2011;Eimer et al, 2012).…”
Section: Introductionmentioning
confidence: 77%
“…It has been shown that seeing a face for longer (Reynolds & Pezdek, 1992) or more often (Xue, Dong, Chen, Lu, Mumford & Poldrack, 2010) can improve subsequent recognition. Furthermore, learning faces alongside semantic or personal information leads to more accurate recognition (Klatzky, Martin & Kane, 1982), and accompanying differences in neural activation (Kaufmann, Schweinberger & Burton, 2009). Faces that are successfully associated with semantic information are recognized more confidently, spanning multiple sessions (Bonner, Burton, Jenkins & McNeill, 2003).…”
Section: Experiments 2: Face Learningmentioning
confidence: 99%
“…Moreover, in this study N250 amplitude further increased with increasing 13 familiarity of the faces over different experimental blocks. Therefore, a larger N250 to 14 different-image, non-immediate repetitions of faces reflects an index of familiarity that can 15 be used to track the establishment of face representations (Kaufmann et al, 2009). At the 16 same time, increasing N250 amplitudes in the course of learning appear to reflect the 17 acquisition of a stable face representation, independent of the repetition of specific images.…”
Section: Introduction 2mentioning
confidence: 99%